5‐Hydroxytryptamine Receptor 1D Aggravates Hepatocellular Carcinoma Progression Through FoxO6 in AKT‐Dependent and Independent Manners. Issue 5 (10th March 2019) - Zuo, Xueliang; Chen, Zhiqiang; Cai, Juan; Gao, Wen; Zhang, Yao; Han, Guoyong; Pu, Liyong; Wu, Zhengshan; You, Wei; Qin, Jianjie; Dai, Xinzheng; Shen, Hongbing; et al.
Abstract : Serotonin and its receptors have been shown to play critical regulatory roles in cancer biology. Nevertheless, the contributions of 5‐hydroxytryptamine 1D (5‐HT1D), an indispensable member of the serotonergic system, to hepatocellular carcinoma (HCC) remain unknown. The present study demonstrated that the 5‐HT1D expression level was significantly up‐regulated in HCC tissues and cell lines. The 5‐HT1D expression level was closely correlated with unfavorable clinicopathological characteristics. Survival analyses show that elevated 5‐HT1D expression level predicts poor overall survival and high recurrence probability in HCC patients. Functional studies revealed that 5‐HT1D significantly promoted HCC proliferation, epithelial‐mesenchymal transition, and metastasis in vitro and in vivo . Mechanistically, 5‐HT1D could stabilize PIK3R1 by inhibiting its ubiquitin‐mediated degradation. The interaction between 5‐HT1D and phosphoinositide‐3‐kinase regulatory subunit 1 (PIK3R1) enhanced the expression of FoxO6 through the PI3K/Akt signaling pathway; FoxO6 could also be directly transcriptionally activated by 5‐HT1D in an Akt‐independent manner. MicroRNA‐599 was found to be an upstream suppressive modulator of 5‐HT1D. Additionally, 5‐HT1D could attenuate tryptophan hydroxylase 1 expression through the PI3K/Akt/cut‐like homeobox 1 axis in HCC. Conclusion : Herein, we uncovered the potent oncogenic effect of 5‐HT1D on HCC by interacting with PIK3R1 to activate the PI3K/Akt/FoxO6 pathway, and provided a potential therapeutic target for HCC.